1997
DOI: 10.1074/jbc.272.31.19621
|View full text |Cite
|
Sign up to set email alerts
|

Rotation of a γ-ε Subunit Domain in the Escherichia coli F1F0-ATP Synthase Complex

Abstract: A triple mutant of Escherichia coli F 1 F 0 -ATP synthase, ␣Q2C/␣S411C/⑀S108C, has been generated for studying movements of the ␥ and ⑀ subunits during functioning of the enzyme. It includes mutations that allow disulfide bond formation between the Cys at ␣411 and both Cys-87 of ␥ and Cys-108 of ⑀, two covalent cross-links that block enzyme function (Aggeler, R., and Capaldi, R. A. (1996) J. Biol. Chem. 271, 13888 -13891). A cross-link is also generated between the Cys at ␣2 and Cys-140 of the ␦ subunit, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
50
0

Year Published

1998
1998
2002
2002

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(52 citation statements)
references
References 36 publications
2
50
0
Order By: Relevance
“…Cross-linking studies (Aggeler et al 1997) have indicated that e is probably a part of the rotor and d belongs to the stator. When an actin ¢lament was bound to e instead of g, the ¢lament also rotated counterclockwise, although the rotary speed was somewhat lower (KatoYamada et al 1998).…”
Section: (D) F O Awaits More Experimentsmentioning
confidence: 99%
“…Cross-linking studies (Aggeler et al 1997) have indicated that e is probably a part of the rotor and d belongs to the stator. When an actin ¢lament was bound to e instead of g, the ¢lament also rotated counterclockwise, although the rotary speed was somewhat lower (KatoYamada et al 1998).…”
Section: (D) F O Awaits More Experimentsmentioning
confidence: 99%
“…Recent evidence strongly suggests that ␥ and probably ⑀ rotate relative to ␣ and ␤ during catalysis (13)(14)(15)(16). Several studies have implied that the ␦ subunit is located near the top of the ␣␤ cluster (17)(18)(19)(20).…”
mentioning
confidence: 99%
“…E. coli strains used were XL1-Blue (Stratagene) for site-directed mutagenesis and for cloning and the unc Ϫ RA1 (29) to express the ATP synthase. Plasmids used were pRA13 (30) containing the wild-type ␤, ␥, and genes and pRA197 (31) containing the wild-type unc operon except that two c subunits were fused through an additional sequence, and a cysteine was introduced in position 42 in the latter of the two c subunits (ccЈ).…”
Section: Methodsmentioning
confidence: 99%